PENGARUH PEMBERIAN KOMPOS LIMBAH KULIT DURIAN TERHADAP PERTUMBUHAN DAN PRODUKSI TANAMAN JAGUNG (ZEA MAYS L.) - IRAWATY ROSALYNE (LP2MTBM MAKARIOZ, 2019)
This research was conducted from January to July 2016 at Simalungun Pematangsiantar University Agricultural Land with an altitude of ± 450 m above sea level. The purpose of this study was to determine the effect of Compost Durian Skin Waste on Corn Plant Growth and Production (Zea mays L).This study uses a non-factorial Randomized Block Design (RBD) consisting of 4 levels, namely: D0 = without the provision of durian skin waste compost, D1 = giving durian skin waste compost of 5 kg / plot, D2 = giving compost of 6 kg durian skin waste / plot, D3 = 7 kg / plot of durian skin waste compost. The parameters observed were plant height (cm), ear length (cm), ear weight per plant (g), dry seed weight per plant (g) and dry seed weight per plot (kg). The data obtained was observed by analysis of variance, while to find out the differences between treatments was tested using the Smallest Significant Difference (LSD) with a confidence interval of 5%.The results of statistical analysis show that durian skin waste compost has a significant effect on all observed parameters. The highest plants at the age of 30 days after planting and 60 days after planting (97.79 cm) and (178.97 cm). The treatment of doses of durian skin waste compost at D3 is the best treatment. The results showed that the longest corn cobs were (19.4 cm), corn cob weight per plant (185.06 gr), dry seed weight per plant (143.30 gr) and dry seed weight per plot (5.02 kg )